Enhancing Access to Education for out-of-school Children in Hard to Reach Communities in Ghana: The ACE experience - Ampiah, J.G.; Fletcher, J.A.; Davis, E.K.; Abreh, M.K. (Journal of Education: Issues and Practice, 2013)
Access to quality Basic Education for all school-age children has been the vision of governments of many developing countries, especially those in sub-Saharan Africa. However, the way to provide access to quality education for all school-age children, especially in the hard-to-reach communities has been a major challenge. This position paper looks at an innovative approach to providing access to quality education in hard- to-reach communities in Northern Ghana by the Alliance for Change in Education (ACE), through the Wing School project. The paper aims to share the good practices of the ACE Wing School model. It highlights the key characteristics of the ACE methodology, approach to access, ACE Wing School approach to quality of learning outcomes, community participation. Challenges of the ACE methodology are highlighted and aspects of the ACE methodology which could be useful for state adoption have been recommended to stakeholders of education in Ghana.
Keywords: Wing school; Hard-to-reach; Community participation; Pupil participation